High Sugar Intake Increases ADHD Symptoms: A Literature Study - Ni Luh Ayu Putu Indah Yulantari; I Gusti Putu Martha Kusuma (International Journal of Public Health Excellence (IJPHE), 2023)
Attention-deficit and hyperactivity disorder (ADHD) is a neurodevelopmental disorder that occurs in 5–12% of children in the world. ADHD has the characteristics of difficulty concentrating (focusing), being easily distracted, not being easily tired, excessive activity, impulsiveness, decreased executive function, fidgeting, excessive talking, difficulty waiting for one's turn, and often disturbing others. External factors that play an important role in the treatment of ADHD are nutrition and diet. Various nutrition experts have stated that nutrition plays an important role in neurodevelopment. Increased consumption of sugar calories is associated with decreased activity in areas associated with dopamine (posterior midbrain, dorsolateral/orbitofrontal cortices) and taste processing areas (postcentral gyrus) during sugar consumption. The method used in this study uses study literature collected from various reference journal articles from 2007–2023 and international journal articles that are interconnected. All the articles obtained state that sugar can disrupt the balance of neurotransmitters in the body of people with ADHD, namely dopamine and norepinephrine, which will increase the symptoms of ADHD. The significance value obtained is below p 0.05, which means that there is an effect of sugar on the symptoms of ADHD. Based on several sources of journal articles, it can be concluded that consuming sugar in children with ADHD will increase the symptoms of ADHD, such as inattentiveness and impulsivity. However, sugar consumption in normal children does not cause ADHD, but it is possible to experience other diseases.